The importance of colonoscopy bowel preparation for the detection of colorectal lesions and colorectal cancer prevention - Sharma, Prateek; Burke, Carol A.; Johnson, David A.; Cash, Brooks D. (Endoscopy International Open, 2020)
Background and study aims Colonoscopy for colorectal cancer (CRC) screening has reduced CRC incidence and mortality and improved prognosis. Optimal bowel preparation and high-quality endoscopic technique facilitate early CRC detection.This review provides a narrative on the clinical importance of bowel preparation for colonoscopy and highlights available bowel preparations.Methods A PubMed search was conducted through June 2019 to identify studies evaluating clinical outcomes, efficacy, safety, and tolerability associated with bowel preparation for CRC screening-related colonoscopy.Results Selecting the optimal bowel preparation regimen is based on considerations of efficacy, safety, and tolerability, in conjunction with individual patient characteristics and preferences. Available bowel preparations include high-volume (4 L) and low-volume (2 L and 1 L), polyethylene glycol (PEG) solutions, sodium sulfate, sodium picosulfate/magnesium oxide plus anhydrous citric acid, sodium phosphate tablets, and the over-the-counter preparations magnesium citrate and PEG-3350. These preparations may be administered as a single dose on the same day or evening before, or as two doses administered the same day or evening before/morning of colonoscopy. Ingesting at least half the bowel preparation on the day of colonoscopy (split-dosing) is associated with higher adequate bowel preparation quality versus evening-before dosing (odds ratio [OR], 2.5; 95 % confidence interval [CI], 1.9−3.4).Conclusions High-quality bowel preparation is integral for optimal CRC screening/surveillance by colonoscopy. Over the last 30 years, patients and providers have gained more options for bowel preparation, including low-volume agents with enhanced tolerability and cleansing quality that are equivalent to 4 L preparations. Split-dosing is preferred for achieving a high-quality preparation.